Prostate-Specific Antigen Increase during Dutasteride to Indicate the Need for Prostate Biopsy: Influence of Prostatic Inflammation. Issue 3 (July 2017) - Sciarra, Alessandro; Maggi, Martina; Fasulo, Andrea; Salciccia, Stefano; Gentile, Vincenzo; Cattarino, Susanna; Gentilucci, Alessandro
Introduction: The aim of this study was to analyze the significance of an increase in total prostate-specific antigen (PSA) serum levels despite dutasteride treatment as a predictor of prostate cancer (PC) at biopsy. We focused our attention on the rate of the first PSA increase and on the influence of prostatic inflammation. Methods: From 2011 to 2016, 365 men with a previous negative prostate biopsy and persistent elevated PSA levels received dutasteride treatment. The population was followed for a range of 12-48 months. Results: One hundred twelve cases with a confirmed PSA increase >0.5 ng/ml over the nadir value during the follow-up were included in Group A and underwent a new prostate biopsy. In Group A, the PSA increase was associated with PC at the re-biopsy in 66% of cases. The percentage of PSA reduction after 6 months of treatment was not a significant indicator of the risk for PC. The distribution of inflammatory infiltrates significantly (p<00.01) varied from positive to negative prostate biopsies. The relative risk for PC at biopsy significantly increased according to PSA level during dutasteride. Conclusions: Treatment with dutasteride can help to analyze PSA kinetic. A persistent prostatic inflammation is a factor able to reduce the performance of PSA kinetic during dutasteride treatment.